2021
DOI: 10.1016/j.ijid.2021.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro activity of linezolid, tedizolid, sutezolid, and delpazolid against rapidly growing mycobacteria isolated in Beijing, China

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“… 15 However, a previous study from Beijing, China, showed high-level MIC values to TZD, in which the TZD MIC 50 and MIC 90 for M. avium and M. intracellulare were 32 and >32 μg/mL, respectively. 23 Therefore, the relative higher MIC values for MAC isolates in our study could have national and geographical reasons such as the high use of antibiotics in China. Furthermore, all studies including ours showed the high MIC values of TZD against MAC; thus, it is necessary to carry out drug sensitivity tests before TZD administration.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“… 15 However, a previous study from Beijing, China, showed high-level MIC values to TZD, in which the TZD MIC 50 and MIC 90 for M. avium and M. intracellulare were 32 and >32 μg/mL, respectively. 23 Therefore, the relative higher MIC values for MAC isolates in our study could have national and geographical reasons such as the high use of antibiotics in China. Furthermore, all studies including ours showed the high MIC values of TZD against MAC; thus, it is necessary to carry out drug sensitivity tests before TZD administration.…”
Section: Discussionmentioning
confidence: 77%
“…This result is consistent with previous studies in which the TZD MIC 50 and MIC 90 were 1-4 and 2-8 μg/mL, respectively. 13,15,[21][22][23] The TZD MIC 50 and MIC 90 for MAC were relatively high at 16 and 32 μg/mL, respectively (Table 2). In a previous study, both the TZD MIC 50 and MIC 90 for MAC were 8 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…This efficiency was less than, but comparable to the commercial herbicide asulam that was lethal at all concentrations tested pre-and post-emergence. Sutezolid 2, a thiomorpholine analogue of linezolid with similar antimicrobial effects, 39 had activity similar to 1. By contrast for 1 and 2, the piperazyl analogue 3 of 1 was inactive (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 19 Our previous study showed that TZD harbors the strongest inhibitory activity against M. abscessus in vitro, while DZD offered the best inhibitory activity against M. fortuitum in vitro. 20 Furthermore, TZD could inhibit the intracellular bacterial population of both M. avium and M. abscessus and had a concentration-dependent synergistic effect against amikacin and ethambutol. 21 Since these new oxazolidinone drugs are currently not in clinical usage or have been recently adopted, therefore, well-recognized susceptibility testing methods for TZD, SZD and DTD have not been developed.…”
Section: Discussionmentioning
confidence: 98%